Epidemiological Characteristics and Transmissibility for SARS-CoV-2 of Population Level and Cluster Level in a Chinese City - Yu, Shanshan; Cui, Shufeng; Rui, Jia; Zhao, Zeyu; Deng, Bin; Liu, Chan; Li, Kangguo; Wang, Yao; Yang, Zimei; Li, Qun; Chen, Tianmu; Wang, Shan (Frontiers in Public Health, 2022)
Background:To date, there is a lack of sufficient evidence on the type of clusters in which SARS-CoV-2 is most likely to spread. Notably, the differences between cluster-level and population-level outbreaks in epidemiological characteristics and transmissibility remain unclear. Identifying the characteristics of these two levels, including epidemiology and transmission dynamics, allows us to develop better surveillance and control strategies following the current removal of suppression measures in China. Methods: We described the epidemiological characteristics of SARS-CoV-2 and calculated its transmissibility by taking a Chinese city as an example. We used descriptive analysis to characterize epidemiological features for COVID-19 in Chaoyang District, Beijing City, China. The SEIAR model was fitted with the dataset, and the effective reproduction number (Reff) was calculated as the transmissibility of a single population. Also, the basic reproduction number (R0) was calculated by definition for three clusters, such as household, factory and community, as the transmissibility of subgroups. Results: The epidemic curve in Chaoyang District was divided into three stages. We included 9 clusters (subgroups), which comprised of 7 household-level and 1 factory-level and 1 community-level cluster, with sizes ranging from two to seventeen cases. For the 9 clusters, the median incubation period was 17.0 days (Interquartile range [IQR]: 8.4-24.0 days [d]), and the average interval between date of onset (report date) and diagnosis date was 1.9 d (IQR: 1.7 to 6.4 d). At the population level, the transmissibility of the virus was high in the early stage of the epidemic (Reff = 4.81). The transmissibility was higher in factory-level clusters (R0 = 16) than in community-level clusters (R0 = 3), and household-level clusters (R0 = 1). Conclusions: In Chaoyang District, the epidemiological features showed multi-stage pattern. Many clusters were reported to occur indoors, mostly from households and factories, and few from the community. The risk of transmission varies by setting, with indoor settings being more severe than outdoor settings. Reported household clusters were the predominant type, but the population size of the different types of clusters limited transmission. The transmissibility was different between a single population and its subgroups, with cluster-level transmissibility higher than population-level transmissibility.